2001
DOI: 10.1159/000050738
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Use and the Utilisation of Drug Help Services by Consumers of the Open Drug Scene in Hamburg

Abstract: In order to describe the patterns of use in the open drug scene in Hamburg, a study was carried out among 616 drug users in the drug scene and in or in the vicinity of low-threshold institutions close to the drug scene in summer 2000. The special focus was on the prevalence of cocaine and crack use as well as on the utilisation of help services for drug users. 80% of the interviewed persons were male, the average age was 32.6 years. They had been using drugs such as heroin or cocaine for an average of 11 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
13
0
5
Order By: Relevance
“…The second group consisted of socially marginalized drug users who belong to the 'old' drug scene of heroin users and who are outside a drug specific treatment. In this group, an increasing use of cocaine has been observed in recent years [4,5]. Socially integrated drug users who are using cocaine mainly in recreational contexts constituted the third target group, since cocaine use in this group seems to play an important role as a part of an occasional use, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The second group consisted of socially marginalized drug users who belong to the 'old' drug scene of heroin users and who are outside a drug specific treatment. In this group, an increasing use of cocaine has been observed in recent years [4,5]. Socially integrated drug users who are using cocaine mainly in recreational contexts constituted the third target group, since cocaine use in this group seems to play an important role as a part of an occasional use, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, intranasal use is still the predominant route of administration for cocaine [3], with the exception of the group of multi-substance dependents [4]. Regarding the somatic consequences of intranasal use, switching to smoking cocarettes may be considered less harmful for cocaine users, who are actually not willing to abstain from cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of distinct health risks and consequences for crack users, for example, that they display overall worse health status than other drug users (Haydon et al, 2005b;Cherubin & Sapira, 1993;Erickson, Butters, McGillicuddy, & Hallgren, 2000;Verthein, Haasen, Prinzleve, Degkwitz & Krausz, 2001). Several studies have shown crack use to be an independent predictor of HCV infection status although there is no clarity at this point as to whether crack use (via paraphernalia sharing) itself functions as a causal pathway for HCV transmission, or rather is a »proxy« of other eleFischer et al | Kokain und Crack Gebrauch bei kanadischen Opioid-Konsumenten…”
Section: Risks and Harms Associated With Cocaine And Crack Usementioning
confidence: 99%